2019
DOI: 10.3390/w11122463
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Investigation of Dew Potential based on Long-Term Model Simulations in Iran

Abstract: Since water shortage has been a serious challenge in Iran, long-term investigations of alternative water resources are vital. In this study, we performed long-term (1979–2018) model simulation at seven locations (costal, desert, mountain, and urban conditions) in Iran to investigate temporal and spatial variation of dew formation. The model was developed to simulate the dew formation (water and ice) based on the heat and mass balance equation with ECMWF-ERA-Interim (European Centre for Medium-Range Weather For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The results from both ex-perimental approaches show that the amount of NRW formed in the non-growing season is higher than that of the growing season. This agrees well with previous findings on the seasonality of dew formation across different climate zones (Zhang et al, 2019;Groh et al, 2019;Atashi et al, 2019). The results from the treatments with elevated temperature demonstrate an impact of warming on the incoming atmospheric water, i.e.…”
Section: Response Of Water Fluxes To Climatic Changessupporting
confidence: 92%
“…The results from both ex-perimental approaches show that the amount of NRW formed in the non-growing season is higher than that of the growing season. This agrees well with previous findings on the seasonality of dew formation across different climate zones (Zhang et al, 2019;Groh et al, 2019;Atashi et al, 2019). The results from the treatments with elevated temperature demonstrate an impact of warming on the incoming atmospheric water, i.e.…”
Section: Response Of Water Fluxes To Climatic Changessupporting
confidence: 92%
“…e resulting long-standing issues with the inefficiency of its water distribution network has particularly affected the agricultural sector (Ashraf et al, 2021). Iran's average annual precipitation over the last 10 years is 250 mm with most of the country receiving <100 mm of rain per year (Atashi et al, 2019). Madani et al (2016) showed that rapid population growth, migration and urbanization, inadequate water distribution infrastructure, water quality degradation, inefficient agriculture, and drought all affect water availability for agriculture.…”
Section: Climate Changementioning
confidence: 99%
“…There are many theoretical calculations which show how it is possible to estimate dew volume on regional and global scale in very similar way. With the help of data from the European Centre for medium-range weather forecasts-reanalysis, the estimation of dew volume was calculated on the territory of Iran (Atashi et al 2019). The global potential for collecting usable water from dew on an artificial collector sheet was investigated by utilizing 34 years of meteorological reanalysis data on global scale.…”
Section: Theoretical Background Of Dew Utilization and Some Limitationsmentioning
confidence: 99%